2017
DOI: 10.4081/monaldi.2017.817
|View full text |Cite
|
Sign up to set email alerts
|

Minute ventilation to carbon dioxide output (V’E/V’CO2 slope) is the strongest death predictor before larger lung resections

Abstract: The minute ventilation to carbon dioxide (CO 2 ) production ratio (V' E /V' CO2 slope) was recently identified as a mortality predictor after lung surgery, but the effect of the resection extent was not taken into account. The aim of this study was to investigate the role of V' E /V' CO2 slope as preoperative mortality predictor depending on the type of surgery performed. Retrospective analysis was performed on 263 consecutive patients evaluated before surgery for lung cancer. Death within 30 days and serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension. 5 Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, 21 and superior predictor to the oxygen uptake efficiency slope in patients with heart failure. 22 TA B L E 4 The association between demographic and clinical with parameters of cardiopulmonary exercise testing (correlation and multivariate regression analyses)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension. 5 Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, 21 and superior predictor to the oxygen uptake efficiency slope in patients with heart failure. 22 TA B L E 4 The association between demographic and clinical with parameters of cardiopulmonary exercise testing (correlation and multivariate regression analyses)…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension . Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, and superior predictor to the oxygen uptake efficiency slope in patients with heart failure …”
Section: Discussionmentioning
confidence: 99%
“…For instance, TORCHIO et al [69] reported that a high V′ E -V′ CO 2 slope was the strongest predictor of mortality after pneumonectomies, a finding extended by MIYAZAKI et al [70] to less extensive anatomical lung resections. ELLENBERGER et al [71] found that a particularly high V′ E /V′ CO 2 (>40) predicted poor survival after radical surgery for lung cancer.…”
Section: Impact Of Copd Comorbidities On V′ E /V′ Comentioning
confidence: 89%
“…18,19 A high VE/VCO 2 slope is known to be associated with a risk of pulmonary arterial hypertension in patients with COPD, 20 and has been suggested as a possible indicator of subclinical heart failure in patients referred for pneumonectomy. 21 The VE/VCO 2 slope is more commonly evaluated in patients with chronic heart failure. Two recent meta-analyses on the effects of exercise training in patients with heart failure also notably failed to show any benefits of exercise training on the VE/VCO 2 slope, even with high-intensity interval training.…”
Section: Discussionmentioning
confidence: 99%